2019
DOI: 10.1080/02705060.2019.1585392
|View full text |Cite
|
Sign up to set email alerts
|

Food habits of three non-native cichlid fishes in the lowermost Chao Phraya River basin, Thailand

Abstract: The food habits of three non-native cichlid fishes, Mayan cichlid (Mayaheros urophthalmus), Mozambique tilapia (Oreochromis mossambicus) and Nile tilapia (O. niloticus), in the lowermost Chao Phraya River basin, Thailand, was examined by stomach contents analysis. The index of preponderance, an index of the importance of prey items, was calculated from two relative metrics of prey quantity: percent frequency and percent volume. The index of niche breadth and the overlap coefficient were calculated to compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…The trophic position occupied by the different size classes is in accordance with previous findings, that O. mossambicus can consume different kinds of prey, such as algae, phytoplankton, zooplankton, insects and fish (Dyer et al, 2013;Zengeya et al, 2011). This study agrees with the finding of Tomojiri et al (2019), who studied the food habits of three alien cichlid fish, namely, Mayan cichlid, Mayaheros urophthalmus, O. mossambicus and Nile tilapia, O. niloticus in the Chao Phraya River basin in Thailand, that detritus was the main food resource, whereas algae and small aquatic animals were secondary prey items. The results obtained from stable isotope and gut content analyses agree with those from previous studies that suggested that G. affinis has a broad dietary niche (Garcia, 1999;Ruehl & DeWitt, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…The trophic position occupied by the different size classes is in accordance with previous findings, that O. mossambicus can consume different kinds of prey, such as algae, phytoplankton, zooplankton, insects and fish (Dyer et al, 2013;Zengeya et al, 2011). This study agrees with the finding of Tomojiri et al (2019), who studied the food habits of three alien cichlid fish, namely, Mayan cichlid, Mayaheros urophthalmus, O. mossambicus and Nile tilapia, O. niloticus in the Chao Phraya River basin in Thailand, that detritus was the main food resource, whereas algae and small aquatic animals were secondary prey items. The results obtained from stable isotope and gut content analyses agree with those from previous studies that suggested that G. affinis has a broad dietary niche (Garcia, 1999;Ruehl & DeWitt, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…For the assessment of the importance of each prey category, the index of preponderance (IOPa) (Sreeraj et al, 2006;Tomojiri et al, 2019) was calculated as:…”
Section: Stomach Content Analysismentioning
confidence: 99%
“…Seasonal and sized based dietary variations of O. niloticus in Lake Shala was studied based on the percent volumetric contribution, frequency of each food item, IOPa (Sreeraj et al, 2006;Tomojiri et al, 2019) and GIIi indices within each length group and seasons (Assis, 1996). For studying seasonal and size based diet variation, fish were classified into five size classes (15-20, 20-25, 25-30 and > 30 cm TL) and two seasons (dry and wet seasons).…”
Section: Estimation Of Seasonal and Size Based Food Habit Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Aided by the transboundary aquarium trade, and unmanaged aquaculture, M. urophthalmus now occurs in inland water bodies in USA (Loftus, 1987), Thailand (Nico, Beamish, & Musikasinthorn, 2007), Sulawesi (Herder et al, 2012), Philippines (Ordonez, Asis, Catacutan, Pena, & Santos, 2015), Singapore (Jaafar, Yeo, Tan, & O'Riordan, 2012;Li et al, 2019;Tan & Tan, 2003;Theng, Sivasothi, & Tan, 2016) and Malaysia (Ng, Ooi, Wong, & Khoo, 2018). Life history and ecological traits including high tolerance to salinity (0-35 ppt), water temperature (14-28°C), resistance to hypoxic conditions (dissolved oxygen <1.0 mg/L) (Martinez-Palacios et al, 1990;Schofield, Loftus, & Fontaine, 2009;Schofield, Loftus, Kobza, Cook, & Slone, 2010), and ability to switch dietary habits (Tomojiri, Musikasinthorn, & Iwata, 2019), makes this cichlid a notorious candidate for future invasions. We report for the first time, the occurrence of M. urophthalmus in South Asia, based on specimens collected from Kerala, India, and highlight the implications of the clandestine trade of exotic aquarium fishes in the region on the increasing biological invasions.…”
Section: Introductionmentioning
confidence: 99%